S32. EFFICACY AND SAFETY OF PALIPERIDONE PALMITATE ONCE-MONTHLY IN PATIENTS WITH SCHIZOPHRENIA WITH LOW, MODERATE, AND HIGH RECENT DISEASE ACTIVITY AT BASELINE - Lynum, Karimah (Schizophr Bull, 2019)
BACKGROUND: Paliperidone palmitate once-monthly (PP1M) is a long-acting injectable formulation that eliminates the need for daily dosing, ensures sustained plasma levels for several weeks, and helps clinicians reliably monitor adherence. We examined the efficacy and safety of PP1M in patients with schizophrenia according to baseline (BL) disease activity, which was based on the frequency of prior psychiatric hospital admissions. METHODS: This was a post hoc analysis of a 17-wk, open-label (OL) treatment period from a large, multicenter, phase 3 noninferiority study (NCT01515423) that compared the efficacy and safety of paliperidone palmitate once-every-3-months and PP1M in patients with schizophrenia. During the 17-wk OL period, patients received flexibly dosed PP1M (day 1 [234 mg]; day 8 [156 mg]; wks 5, 9, and 13 [78, 117, 156, or 234 mg]). Patients were grouped according to the number of hospital admissions for psychosis that occurred 24 months before study entry: no prior hospitalizations (low activity), 1 prior hospitalization (moderate activity), and ≥2 prior hospitalizations (high activity). Assessments included change in Positive and Negative Syndrome Scale (PANSS) total scores, change in Clinical Global Impression-Severity (CGI-S) scores, and the percentage of patients who attained symptomatic remission (defined as a score ≤3 on the following PANSS symptom score items: P1 [delusions], P2 [conceptual disorganization], P3 [hallucinatory behavior], N1 [blunted affect], N4 [social withdrawal], N6 [lack of spontaneity], G5 [mannerisms/posturing], and G9 [unusual thought content]) at OL end point (wk 17). Subgroup differences were examined using ANCOVA models for continuous end points and by the Cochran-Mantel-Haenszel test for categorical variables. No adjustments were made for multiplicity as the OL period was used to determine acceptability for entry to the double-blind period. RESULTS: Of 1,146 patients, 450 (39.3%) had no prior hospitalizations, 426 (37.2%) had 1 prior hospitalization, and 270 (23.6%) had ≥2 prior hospitalizations within the previous 24 months. BL demographics and disease characteristics were similar between groups. Mean age ranged from 37.6 to 41.0 years, patients were predominantly male (range, 51.6%-58.9%), and most were from non–European Union/non–United States regions (range, 51.5%-60.6%). For low, moderate, and high disease activity groups, mean [SD] total PANSS scores were 85.8 (10.51), 85.6 (10.74), and 86.0 (11.3), respectively; mean (SD) CGI-S scores were 4.5 (0.67), 4.4 (0.70), and 4.4 (0.67), respectively. In each disease activity group, statistically and clinically meaningful improvements from BL were observed in all efficacy measures at all time points during the 17-wk treatment period. At OL end point, mean changes from BL in PANSS total scores were -20.5, -20.1, and -18.3 in the low, moderate, and high disease activity groups, and mean changes from BL in CGI-S scores were -1.1, -1.0, and -0.9, respectively; there was no statistically significant difference in PANSS total scores or CGI-S scores between disease activity groups. The percentages of patients who attained symptomatic remission at the OL end point were 49.4%, 53.1%, and 49.1%, respectively. The most common adverse events (≥5% in any group) were insomnia, anxiety, akathisia, injection site pain, nasopharyngitis, and weight increase. DISCUSSION: Findings from the 17-wk OL period demonstrated that treatment with PP1M produced a rapid, beneficial effect in patient symptom scores that was significant from week 1 onward. PP1M was rapidly effective in patients with schizophrenia regardless of BL disease activity. Safety was consistent with previous acute trials evaluating PP1M.